2004
DOI: 10.1038/sj.npp.1300450
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nicotine on Cognitive Deficits in Schizophrenia

Abstract: Several lines of evidence suggest a pathophysiological role for nicotinic receptors in schizophrenia. Activation by nicotine alters physiological dysfunctions, such as eye movement and sensory gating abnormalities, but effects on neuropsychological performance are just beginning to be investigated. Nicotine-induced desensitization and the well-known tachyphylaxis of nicotinic receptors may confound such efforts. In all, 20 schizophrenics, 10 smokers, and 10 nonsmokers were assessed following the administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
161
3
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 224 publications
(176 citation statements)
references
References 58 publications
(68 reference statements)
8
161
3
3
Order By: Relevance
“…There is increasing evidence that nAChR stimulation has beneficial effects on cognitive function in schizophrenia, possibly via presynaptic modulation of dopamine and/or glutamate release (McGehee et al, 1995;George et al, 2000;Picciotto et al, 2000;Wonnacott et al, 2000). The administration of both short-and long-acting preparations of nicotine to individuals with schizophrenia has been associated with improved neuropsychological performance (Levin et al, 1996b;Depatie et al, 2002;Smith et al, 2002Smith et al, , 2006Harris et al, 2004;Jacobsen et al, 2004;Myers et al, 2004). Acute administration of the selective a7nAChR partial agonist, DMXB-A, improved P50 gating compared with placebo (Olincy et al, 2006) and administration of the nAChR antagonist, mecamylamine, blocked smoking-associated improvements in performance on attentional and visuospatial working memory (VSWM), implying that nAChR activation mediates smoking-related cognitive enhancement (Sacco et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is increasing evidence that nAChR stimulation has beneficial effects on cognitive function in schizophrenia, possibly via presynaptic modulation of dopamine and/or glutamate release (McGehee et al, 1995;George et al, 2000;Picciotto et al, 2000;Wonnacott et al, 2000). The administration of both short-and long-acting preparations of nicotine to individuals with schizophrenia has been associated with improved neuropsychological performance (Levin et al, 1996b;Depatie et al, 2002;Smith et al, 2002Smith et al, , 2006Harris et al, 2004;Jacobsen et al, 2004;Myers et al, 2004). Acute administration of the selective a7nAChR partial agonist, DMXB-A, improved P50 gating compared with placebo (Olincy et al, 2006) and administration of the nAChR antagonist, mecamylamine, blocked smoking-associated improvements in performance on attentional and visuospatial working memory (VSWM), implying that nAChR activation mediates smoking-related cognitive enhancement (Sacco et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, many studies investigating the effects of nicotinic stimulation in schizophrenia have been conducted in smokers who have undergone a brief period of abstinence from smoking prior to testing of nicotine effects. Under such circumstances, cognitive benefits observed following the nicotine administration may be confounded by reversal of nicotine withdrawal symptoms or limited by tachyphylaxis (Harris et al, 2004). We, therefore, performed the following study to investigate the acute effects of nicotine on cognition in nonsmokers with schizophrenia and healthy controls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attentional improvement by nicotinic agents may be a key therapeutic effect for these psychiatric disorders [83,84]. It has been demonstrated that smoking withdrawal induced deficits in both attentional performance and spatial working memory in patients with schizophrenia [85].…”
Section: The Potential Of Nicotinic Treatment For the Cognitive Impaimentioning
confidence: 99%
“…In a complementary fashion, nicotinic blockade caused significant deficits in the N-back task [91].. Nicotine nasal spray has been shown to improve spatial organization and also improve memory in people with schizophrenia [92,93]. Nicotine also improves eye tracking, memory and attentional function in schizophrenia [84,85,88,92]. Nicotine skin patch treatment in healthy volunteers significantly improved the speed of pre-attentive sensory processing as indexed by mismatch negativity to auditory stimuli in an oddball paradigm [94] Specific nicotinic receptors may be more promising for the improving aspects of cognition in people with schizophrenia .…”
Section: The Potential Of Nicotinic Treatment For the Cognitive Impaimentioning
confidence: 99%